Latent tuberculosis infection screening in persons newly-diagnosed with HIV infection in Italy: A multicentre study promoted by the Italian Society of Infectious and Tropical Diseases. (March 2020) - Goletti, Delia; Navarra, Assunta; Petruccioli, Elisa; Cimaglia, Claudia; Compagno, Mirko; Cuzzi, Gilda; De Carli, Gabriella; Fondaco, Laura; Franzetti, Fabio; Giannetti, Alberto; Gori, Andrea; Lapadula, Giuseppe; et al.
Highlights: Latent tuberculosis infection (LTBI) screening was performed in only 65.5% of newly diagnosed HIV-infected patients. LTBI tests were mainly requested for patients born outside Italy. The majority of the LTBI subjects came from countries with a high TB prevalence. New guidelines are needed to support LTBI screening. Abstract: Background: The Italian Society of Infectious and Tropical Diseases performed a survey on the application of guidelines for the management of persons living with HIV (PLWH), to evaluate current practice and the yield of screening for latent tuberculosis infection (LTBI) in newly-diagnosed PLWH; in addition, the offer of preventive therapy to LTBI individuals and the completion rate were analysed. Materials and methods: Newly-diagnosed PLWH in nine centres were evaluated retrospectively (2016/2017) using binary and multinomial logistic regression to identify factors associated with LTBI diagnostic screening and QuantiFERON (QFT) results. Results: Of 801 patients evaluated, 774 were studied after excluding active TB. LTBI tests were performed in 65.5%. Prescription of an LTBI test was associated with being foreign-born (odds ratio (OR) 3.19, p  < 0.001), older (for 10-year increments, OR 1.22, p  = 0.034), and having a CD4 count <100 cells/mm 3 vs ≥500 cells/mm 3 (OR 2.30, p  = 0.044). LTBI was diagnosed in 6.5% of 495 patients evaluated by QFT. Positive results were associated with being foreign-born (relative risk ratio (RRR) 30.82, p  < 0.001), older (for 10-year increments, RRR 1.78, p  = 0.003), and having a high CD4 count (for 100 cells/mm 3 increments, RRR 1.26, p  < 0.003). Sixteen LTBI individuals started TB preventive therapy and eight completed it. Conclusions: LTBI screening is inconsistently performed in newly-diagnosed PLWH. Furthermore, TB preventive therapy is not offered to all LTBI individuals and compliance is poor.